The talent project and the validation of standards for the identification of student-athlete talent - Vicari, Domenico Savio Salvatore; Bianco, Antonino; Albanese, Martina; Capranica, Laura; Doupona, Mojca; Koutavelis, Epameinondas; Alexandrou, Georgia; Tsivitanidou, Olia; Gutović, Tea; Zelić, Ivica; Čular, Dražen; Mujkic, Dino; et al. (Frontiers in Sports and Active Living, 2025)
IntroductionThe aim of the TALENT project is to promote equality in education, prevent exclusion, support dual careers (sport and school), create new role models for the benefit of young talents and prepare them for lifelong learning and professional sport from an early age. It is promoted by a European consortium of 7 partner institutions and runs from December 2022 to May 2025. It consists of five work packages. In the first work phase, developing the WP2 (from December 2022 to October 2023), under the coordination of UNIPA, NIS University, KMOP and EAS standards for talent recognition were identified and validated.MethodsInitially, 12 focus groups were conducted with teachers (77 teachers) and coaches (73 coaches) on creating talent identification standards; subsequently, workshops were held with dual career experts to validate these standards. This was a key piece of work that enabled the establishment of clear guidelines and protocols to identify and support talented young people in their dual careers.ResultsA final list of 41 shared statements was identified: 20 related to teachers and 21 related to coaches. For example, teachers emphasized the need for multidisciplinary approaches and early identification of talent, while coaches underlined the importance of psychological readiness and collaboration with schools and families.DiscussionThese statements not only provide structured reference points for talent identification but also highlight actionable needs across educational and sport systems. As such, they represent a solid foundation for developing standard operating procedures in talent recognition and dual career support.